IMPLEMENTASI KEBIJAKAN PEMBANGUNAN INFRASTRUKTUR LINGKUNGAN DENGAN POLA ORGANISASI MASYARAKAT - Putra, Dinda Syufradian (Jurnal Ilmu Administrasi Negara, 2016)
Implementation of the Environment Policy of Infrastructure Development with the Pattern of Community Organizations. This study aims to determine the implementation of the environmental policy of infrastructure development with the pattern of local community organizations District of Pekanbaru City. The informants are Chairman of the District of Pekanbaru City CSO, Head of Pekanbaru City, Electric Companion (TPM) and the District of Pekanbaru City PPTK environmental infrastructure development activities with the pattern of OMS 2013. Data collection techniques used in this research is observation, interview and documentation with technical analysis of data using an interactive model. The result showed that the implementation of the policy by the Environmental Infrastructure Development Patterns Local Community Organizations (CSOs) District of the city of Pekanbaru Pekanbaru City in 2013 is not feasible because there are many problems related systems and rules as well as the resources to support the implementation of policies.